Infected bone defect healing could be complicated due to more delayed responses to antibiotic therapy in ovariohysterectomized rats - Hesaraki, Saeed (Archives of Veterinary Science, 2025)
As females reach old age and menopause, bone fracture has become one of the most common conditions, and its infection has become a threat to the lives of the elderly. The aim of this study was to investigate whether the consequences of microbial infection of the fracture site with fracture-induced infection and its repair in a person with decreased steroid hormones due to ovariohysterectomy are worse than in a normal person's bone. A total of 36 six-month-old Sprague-Dawley (SD) rats were divided into six groups: sham (defect creation only), group I (defect development + infection), group IA (defect creation + infection + antibiotic treatment), group O (ovariohysterectomy three months before defect creation + defecting) , the OI group (ovariohysterectomy three months before defect creation + defecting + infection), and the OIA group (ovariohysterectomy three months before defect creation infection + defecting + infection + antibiotic treatment). A 2 mm defect in the femur's diaphysis was used to perform the fracture. An inoculation of 4 × 104 colony-forming units (CFU)/ml of Staphylococcus aureus was implemented. On the 30th and 60th days, five rats were randomly selected from each group, and blood samples were taken directly from the heart into a tube during euthanasia for TNFα and IL-6 serum level evaluation. After necropsy, samples were taken from the defect site for H&E staining, and culturing agar. Agar culture analysis showed that the OI group had a higher bacterial load in the bone compared to the I group on both days. The OI group showed a wider level of callus and inflammation than even the I group, but in terms of bone formation, it was significantly (p = 0.02) weaker than the I group. Serum findings showed a significant increase in TNF-α level in the OI group compared to the O group on day60. We observed a significant decrease in bone bacterial load and increased healing in IA compared to I, but not in OI compared to OIA. The animal that had ovariohysterectomy had a more severe infection in its broken bone, resulting in increased bone lysis and a greater bacterial load. Additionally, the healing of the fracture was linked to a longer delay. Systemic antibiotics, but not those given to animal bone that had undergone ovariohysterectomy, greatly decreased the bacterial load and improved the quality and strength of the callus in normal bone that had been infected by a fracture.